Never Give Up: Lesson learned from a severe COVID-19 patient (2020)
COVID-19 pandemic is causing major health consequences in affected persons needing hospital admission. Since the first epidemic outbreak in China we have learned that several factors including older age, comorbidities and individual immunological responses to infection may differently address the risk of disease progression and outcome.1 Moreover, there is now quite a unanimous consensus that mortality rate of critically ill patients with SARS-CoV2 pneumonia admitted to Intensive Care Unit (ICU) is really considerable2 and even a slightly higher than that recorded in patients with moderate to severe Acute Respiratory Distress Syndrome (ARDS).